79.5k views
1 vote
What should be the first step in adding these equations to eliminate y

8x+3y= 2
+ 4x-by=-7

User Dyao
by
6.4k points

1 Answer

7 votes

Answer:

Explanation:

Are you sure you wanted that "b" in the second equation?

If so, here's how we eliminate y:

1) Multiply the first equation by b: 8bx + 3by = 2b

2) Multiply the second equation by 3: 12x - 3by = -21

3) Combine these two results. We get:

(8b + 12)x = 2b - 21

Here we have eliminated y, but still have an equation in two variables, b and x.

User Bensie
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.